EMPLOYEE ENGAGEMENT AND MECHANICAL EXPERIENCES AS PERFORMANCE INDICATORS : A STUDY OF MECHANICAL EMPLOYEES OF PT BAS, KARAWANG, INDONESIA - Rahman Hakim, Arif; Mora, Linda; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Employees with high engagement to the company they work for, will provide a lot of benefits to the company such as productivity levels, good service to customers and low turnover or exit of employees in the company, one measure of the performance of a mechanic at PT. BAS is Mechanical Experiences, which is one of the criteria to see individuals in work. Seeing the above phenomenon, then this research is done to know there is a relationship between Employee Engagement with Mechanical Experiences as performance indicator at PT. BAS. The subjects sampled in this study are employees who work in PT. BAS and located in South Kalimantan. The number of samples used for this research is 52 employees. The sample technique used in this research is NonProbability Sampling, with Convenience Sampling method. Using the Product Moment from Pearson, obtained coefficient of expression of an employee engagement with mechanical experience of - 0.098 and sig = 0.489 with p> 0,05. Referring to the result of data analysis that has been described, it can be concluded that there is no significant relationship between employee engagement with mechanical experience in mechanical employees at PT. BAS.